2015
DOI: 10.1002/ajmg.b.32326
|View full text |Cite
|
Sign up to set email alerts
|

On the role of NOS1 ex1f‐VNTR in ADHD—allelic, subgroup, and meta‐analysis

Abstract: Attention deficit/ hyperactivity disorder (ADHD) is a heritable neurodevelopmental disorder featuring complex genetics with common and rare variants contributing to disease risk. In a high proportion of cases, ADHD does not remit during adolescence but persists into adulthood. Several studies suggest that NOS1, encoding nitric oxide synthase I, producing the gaseous neurotransmitter NO, is a candidate gene for (adult) ADHD. We here extended our analysis by increasing the original sample, adding two further sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 47 publications
2
14
0
4
Order By: Relevance
“…We replicated previously observed associations of NOS1 with specifically hyperactive/impulsive and total ADHD symptoms, but not the inattentive symptoms (Reif et al., ; Weber et al., ) in an independent sample. These findings extend previous findings by showing that this association is also observed in children and adolescents.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We replicated previously observed associations of NOS1 with specifically hyperactive/impulsive and total ADHD symptoms, but not the inattentive symptoms (Reif et al., ; Weber et al., ) in an independent sample. These findings extend previous findings by showing that this association is also observed in children and adolescents.…”
Section: Discussionsupporting
confidence: 90%
“…The association of NOS1 genotype and WM properties was only present in females. A female specificity of the NOS1 effects was indeed expected based on the earlier studies linking the exon 1f variant to ADHD status and ADHD-like symptoms (Reif et al, 2009;Weber et al, 2015). One possible explanation could be given by the fact that the promoter region of exon 1f harbours an oestrogen binding site (Reif et al, 2009), and a link between oestrogen and upregulation of nitric oxide synthases has indeed been found (Nuedling et al, 2001).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Despite this considerable heritability, the identification of risk genes has been challenging [3,7], and one reason for this could be the genetic complexity of the disease. Identified candidate genes so far mainly belong to monoaminergic neurotransmitter pathways, especially dopaminergic and serotonergic signaling [8][9][10][11][12]. Different (hypothesis-free) approaches, including genomewide linkage analyses and genome-wide association studies (GWASs), have been performed in order to detect additional genetic factors for ADHD.…”
mentioning
confidence: 99%
“…In addition to this, we also included genes with reported and replicated evidence for association with ADHD from more recent studies. These included two meta-analytic studies (Pan et al, 2015;Wu et al, 2012), a research article (Ribases et al, 2011), and the more recently observed replicated candidate genes NOS1 and SLC9A9 (Stergiakouli et al, 2012;Weber et al, 2015) (total number of candidate genes = 10; Table 1). A recent overview of these ADHD candidate genes has been published by Hawi et al (2015).…”
Section: Candidate Gene Selection For Adhd Asd and Id Studiesmentioning
confidence: 99%